Evaluation of Housing Product Quality Using the Importance-Performance Analysis Method at PT. Galaxy Alam Semesta - Albertus Denny Prasetya; Farida Rachmawati (Publikasi Indonesia, 2024)
Government support for the property sector through incentive policies, such as the Ministry of Finance Regulation on Government-Borne Value Added Tax (VAT-GOV) on properties, was reintroduced in 2024 to boost economic growth, focusing on the delivery of new landed houses and new apartment units. In this context, property and real estate companies are required to maintain customer satisfaction, which is the key to the company's success. Customer satisfaction not only reflects product quality but also influences the company's brand image. To understand customer satisfaction with product quality, particularly landed houses, PT. Galaxy Alam Semesta conducts periodic surveys of its customers. However, survey results from the first semester of 2023 indicated that customer satisfaction with the quality of houses was still below the company's standards. Therefore, this research aims to evaluate the quality of PT. Galaxy Alam Semesta's houses using the Importance-Performance Analysis method. This research will identify attributes that need quality improvement priority, with the hope of enhancing customer satisfaction and the company's image, as well as utilizing the House of Quality to determine the priority of these improvement proposals. The analysis results indicate that the attributes requiring quality improvement priority are even and non-streaky paint, straight wall corners, even wall and ceiling surfaces, smoothly and easily operable doors and windows, neat and even paint and sealant, even tile installation, and precise and neat installation of door and window accessories. From the analysis of the proposed improvement, five main priorities were identified: increasing the frequency of supervision and inspection to ensure compliance with quality standards, setting limits on the number of units overseen by building supervisors, using higher quality paint, evaluating the quality of door accessories and tile materials, and conducting regular evaluations and selections of contractors.